Research perspectives: The 2013 AAOS/ORS research symposium on Bone Quality and Fracture Prevention. Issue 7 (2nd April 2014) - Donnelly, Eve; Lane, Joseph M.; Boskey, Adele L.
ABSTRACT Bone fracture resistance is determined by the amount of bone present ("bone quantity") and by a number of other geometric and material factors grouped under the term "bone quality." In May 2013, a workshop was convened among a group of clinicians and basic science investigators to review the current state of the art in Bone Quality and Fracture Prevention and to make recommendations for future directions for research. The AAOS/ORS/OREF workshop was attended by 64 participants, including two representatives of the National Institutes of Arthritis and Musculoskeletal and Skin Diseases and 13 new investigators whose posters stimulated additional interest. A key outcome of the workshop was a set of recommendations regarding clinically relevant aspects of both bone quality and quantity that clinicians can use to inform decisions about patient care and management. The common theme of these recommendations was the need for more education of clinicians in areas of bone quality and for basic science studies to address specific topics of pathophysiology, diagnosis, prevention, and treatment of altered bone quality. In this report, the organizers with the assistance of the speakers and other attendees highlight the major findings of the meeting that justify the recommendations and needs for this field. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:855–864, 2014.